2013
DOI: 10.1089/vim.2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ljungan Virus Antibodies, HLA-DQ8, and Insulin Autoantibodies in Newly Diagnosed Type 1 Diabetes Children

Abstract: Environmental factors, including viral infections, may explain an increasing and fluctuating incidence of childhood type 1 diabetes (T1D). Ljungan virus (LV) isolated from bank voles have been implicated, but it is unclear whether LV contributes to islet autoimmunity, progression to clinical onset, or both, of T1D. The aim was to test whether LV antibodies (LVAb) were related to HLA-DQ and islet autoantibodies in newly diagnosed T1D patients (n = 676) and controls (n = 309). Patients, 0-18 years of age, diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 46 publications
4
28
1
Order By: Relevance
“…The Finnish study used the same LV isolate (LV 87‐012G) as in the present study to determine LVA by indirect immunofluorescence in infected cell‐lines. The RBA in the present study is based on the LV 87‐012G cDNA [Niklasson et al, ], with the difference that the cDNA was re‐cloned into the high efficiency expression vector TnT [Nilsson et al, ]. In the Finnish bank voles LVA, detected by immunofluorescence, was found in 18% of the animals, which is comparable to the upper quartile of LVA detected in the RBA in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Finnish study used the same LV isolate (LV 87‐012G) as in the present study to determine LVA by indirect immunofluorescence in infected cell‐lines. The RBA in the present study is based on the LV 87‐012G cDNA [Niklasson et al, ], with the difference that the cDNA was re‐cloned into the high efficiency expression vector TnT [Nilsson et al, ]. In the Finnish bank voles LVA, detected by immunofluorescence, was found in 18% of the animals, which is comparable to the upper quartile of LVA detected in the RBA in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…In humans, previous studies on Swedish children and young adults (0–18 years old) indicate that children with newly diagnosed type 1 diabetes had higher levels of LVA than healthy controls, suggesting that LV could possibly contribute to type 1 diabetes in humans [Nilsson et al, , , ]. These studies also implied that LVA levels were higher in young children and that the incidence of type 1 diabetes seemed to co‐vary with subjects with high LVA levels [Nilsson et al, , , ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This virus seems to be especially diabetogenic when the infection is combined with stress, which makes it more interesting as stress for several reasons is suspected to contribute to development of T1D in humans . As antibodies against Ljungan virus seem to be quite common in children with diabetes even though no Ljungan virus RNA was discovered in stool samples from a Norwegian type 1 diabetes cohort, it cannot be excluded that this virus plays a role for the development of some cases of T1D. As the virus is found in rodents we found it relevant to look into the registration of pet animals which the mothers of ABIS babies made in the birth questionnaire when the ABIS children were born October 1, 1997 to October 1, 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Ljungan virus has also been identified in several other species of voles, lemmings as well as yellow‐neck mouse (Apodemus), a hamster relative . Particular attention was paid when an epidemiological association between the periodic increase in number of lemmings and similar variation in incidence of T1D the following years, and antibodies to the virus were found to be quite common in diabetic children . It has been suggested that LV is involved in the pathogenesis of diabetes in BB‐rats .…”
Section: Introductionmentioning
confidence: 99%